Enantioselective dearomative [3+2] cycloaddition of 2-nitrobenzofurans with aldehyde-derived Morita–Baylis–Hillman carbonates. Issue 62 (15th July 2019) - Yang, Xin-He; Li, Jian-Ping; Wang, Dong-Chao; Xie, Ming-Sheng; Qu, Gui-Rong; Guo, Hai-Ming
Abstract : The phosphine-catalyzed asymmetric dearomative [3+2] cycloaddition of 2-nitrobenzofurans with aldehyde-derived MBH carbonates or allenoates was developed. Abstract : The phosphine-catalyzed asymmetric dearomative [3+2] cycloaddition of 2-nitrobenzofurans with aldehyde-derived Morita–Baylis–Hillman (MBH) carbonates or allenoate was developed. The reaction with MBH carbonates resulted in a series of cyclopentabenzofurans containing three contiguous stereocenters with good to high yields, diastereoselectivities and enantioselectivities. The use of allenoate also gave the target product with moderate enantioselectivity.